Into the Amazon : the life of Cândido Rondon, trailblazing explorer, scientist, statesman, and conservationist - Rohter, Larry, 1950- (W.W. Norton & Company, 2023)
A comprehensive biography of the Indigenous Brazilian explorer, scientist, statesman and conservationist who guided Theodore Roosevelt on his journey down the River of Doubt chronicles his extraordinary career and his many achievements, including three nominations for the Nobel Peace Prize.